Pendampingan Pengemasan Dan Pelebelan Hasil Produksi Pupuk Organik Cair (POC) Limbah Ikan Kelompok Wanita Pesisir Desa Kuranji - Eko Supriastuti; Farah Ainun Jamil; Mutiara Mita Kasia; Dewi Rispawati (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Kuranji Village is a coastal village with abundant fishery resources. The community's fishing activities produce fish waste, which has been processed into Liquid Organic Fertilizer (POC), which is beneficial for the agricultural sector and has significant economic value due to its rich nutrient content. Although the POC production process has been implemented, the resulting product is still marketed simply with basic packaging and lacks informative and attractive product labels. The women's fisherfolk group lacks adequate knowledge and skills regarding proper packaging techniques and product label design. The purpose of this activity is to improve the knowledge and skills of group members in packaging, labeling, branding, and developing a business for POC products that are good, attractive, and meet marketing standards, thus increasing their sales value. The results of this community service activity indicate an increase in participants' knowledge and skills in packaging POC products more neatly, hygienically, and attractively, thereby improving product quality and added value. Through label design training, participants are also able to produce informative labels with clear product identification, thereby increasing consumer confidence in the products. Product branding training provided participants with an understanding of the importance of building a brand and product image as a strategy to increase market competitiveness. Previously marketed simply, POC products now have a stronger identity and are easily recognized by consumers. Short-term and long-term business development mentoring activities successfully improved the group's ability to develop more systematic business plans, ranging from product quality improvement, marketing expansion, institutional strengthening, and sustainable business development.